2022
DOI: 10.3390/ma15113926
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Ablated Copper Surface as a Substrate for a MoS2-Based Hydrogen Evolution Reaction Electrocatalyst

Abstract: One of the methods to improve the performance of a heterogeneous electrocatalyst is the dispersion of a catalytic material on a suitable substrate. In this study, femtosecond laser ablation was used to prepare very rough but also ordered copper surfaces consisting of vertical, parallel ridges. Then, a molybdenum sulfide coating was electrochemically deposited onto these surfaces. It was observed by profilometry that the average roughness of the surface after coating with MoS2 had decreased, but the developed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Due to the random nature of plasma discharges in PEO, MoS x should not coat the anode surface evenly. Previous experience has shown that scanning electrochemical microscopy (SECM) can be used to measure the local hydrogen evolution activity of MoS 2 on complex surface structures [62]. The substrate generation-tip collection (SG-TC) mode is used, wherein the substrate generates hydrogen by the Heyrovsky step (Equation ( 8)) and the probe oxidizes it (Equation ( 9)):…”
Section: Scanning Electrochemical Microscopy Of Hermentioning
confidence: 99%
“…Due to the random nature of plasma discharges in PEO, MoS x should not coat the anode surface evenly. Previous experience has shown that scanning electrochemical microscopy (SECM) can be used to measure the local hydrogen evolution activity of MoS 2 on complex surface structures [62]. The substrate generation-tip collection (SG-TC) mode is used, wherein the substrate generates hydrogen by the Heyrovsky step (Equation ( 8)) and the probe oxidizes it (Equation ( 9)):…”
Section: Scanning Electrochemical Microscopy Of Hermentioning
confidence: 99%